A survey of moving target traveling salesman problem - Uçar, Ukbe; İšleyen, Selçuk Küršat (Nova Science Publishers, Inc., 2019)
The Moving-Target Traveling Salesman Problem is an NP-Hard problem that has been extensively studied in recent years. In this problem, it is tried to destroy targets moving at a constant speed by a pursuer within minimum task time. The problem is widely used in many applications such as military operations, scheduling of robotic systems, security camera routing and marine surveillance operations. Furthermore, interest in this problem is expected to grow in parallel with accelerating transition of production systems to Industry 4.0 and the developments in modern warfare technologies. This paper analyzed studies performed on the Moving-Target Traveling Salesman Problem between 1995 and 2019. The examined studies were systematically classified according to their real-life applications, and the solution methodologies used for the problem were also described. Finally, a number of predictions were made concerning the other versions of the problem and the problem’s future areas of application. In addition, this study is known as the first survey study about MTTSP. © 2020 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Aerospace science and technology; Dynamic systems; Maritime surveillance problem; Moving-target traveling salesman problem; Unmanned aerial vehicles